2012
DOI: 10.1186/1743-422x-9-110
|View full text |Cite
|
Sign up to set email alerts
|

Loop-mediated isothermal amplification for the detection of goose circovirus

Abstract: BackgroundGoose circovirus (GCV) presents an immunosuppressive problem in production of geese. The infection’s clinical symptoms include growth retardation or feathering disorders but the infection process may remain non-symptomatic what makes the infected birds more susceptible for secondary viral, bacterial and fungal infections. Diagnosis of GCV infection is made by histopathological examination, dot blot hybridization, polymerase chain reaction (PCR) and real-time PCR. However these techniques require appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
0
26
0
2
Order By: Relevance
“…The explanation for these results is the mechanism of LAMP that requires the use of outer and inner primers thus following very sensitive nested-PCR. The third pair of loop primers is not necessary for LAMP progress but significantly accelerates the reaction (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The explanation for these results is the mechanism of LAMP that requires the use of outer and inner primers thus following very sensitive nested-PCR. The third pair of loop primers is not necessary for LAMP progress but significantly accelerates the reaction (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…The authors obtained positive results after 20 min at 65°C (13). The specificity of the reaction was tested using different pathogens (Aleutian disease virus-ADV, Newcastle disease virus-NDV, Pasteurella multocida, Salmonella Enteritidis, Escherichia coli), while the sensitivity was tested using serial 10-fold dilutions of plasmid DNA (pVP3 2.8 x10 0 -2.8x10 11 ). Similar to our data, the authors have demonstrated that LAMP is as specific as PCR (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Omawiane techniki genetyczne, coraz częściej i szerzej zastępują testy opierające się na ocenie właściwościach fenotypowych drobnoustrojów i reakcjach antygen-przeciwciało (3,6,23,24). Dotychczas opracowano wiele technik wykrywania i analizy materiału genetycznego bakterii i wirusów, z których najbardziej istotnymi wydają się: łańcuchowa reakcja polimerazy (polymerase chain reaction -PCR) (25,26,36) wraz z jej pochodnymi modyfikacjami oraz techniki amplifikacji DNA w warunkach stałej temperatury (29,40).…”
Section: Artykuł Przeglądowy Reviewunclassified
“…For example, the LAMP reaction does not require expensive laboratory equipment such as a thermal cycler; the result is obtained within 1 h or less; the result shows specificity because 4-6 primers are required that hybridize against 6-8 distinct sequences in the target DNA; and the amplified products are visualized simply through an increase in turbidity or change in color detected through the use of an intercalating fluorescent dye such as SYBR Green I (Mori et al, 2001;Notomi et al, 2000). LAMP-based assays have been used for rapid and sensitive detection of microorganisms and harmful microalgae (Chen & Cui, 2009;Chen et al, 2013;Nagai et al, 2012;Picon-Camacho et al, 2013;Woźniakowski et al, 2012;Zhang et al, 2013Zhang et al, , 2014. The aim of the present study was to develop a sensitive, specific, and cost-effective LAMP-based approach for the detection of the harmful jellyfish C. nozakii.…”
Section: Introductionmentioning
confidence: 99%